2015
DOI: 10.3133/ds950
|View full text |Cite
|
Sign up to set email alerts
|

Mercury, monomethyl mercury, and dissolved organic carbon concentrations in surface water entering and exiting constructed wetlands treated with metal-based coagulants, Twitchell Island, California

Abstract: Cover. Photographs taken by Tamara Kraus, U.S. Geological Survey. Top Left: Coagulation system designed and built by Bachand and Associates. Bottom Left: Water samples collected from the inlets of the experimental wetland cells: 6 (control, not treated), 5 (iron treatment) and 4 (aluminum treatment). Right: One of the constructed wetlands cells, Twitchell Island, California.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Methods to measure nutrients ( NH4+, NO3, nitrite [NO 2 − ], and soluble reactive phosphorus [SRP]), dissolved inorganic carbon (DIC), and Chl a in the discrete water samples followed Parker et al (2012 a ; see Supporting Information for details). DOC concentrations were determined by high‐temperature catalytic combustion (Stumpner et al ). TSS concentrations were determined by filtering known volumes of sample water through 0.3 μ m glass fiber filters, then measuring the dry weight of material retained on the filter.…”
Section: Methodsmentioning
confidence: 99%
“…Methods to measure nutrients ( NH4+, NO3, nitrite [NO 2 − ], and soluble reactive phosphorus [SRP]), dissolved inorganic carbon (DIC), and Chl a in the discrete water samples followed Parker et al (2012 a ; see Supporting Information for details). DOC concentrations were determined by high‐temperature catalytic combustion (Stumpner et al ). TSS concentrations were determined by filtering known volumes of sample water through 0.3 μ m glass fiber filters, then measuring the dry weight of material retained on the filter.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, NRZs can affect concentrations of dissolved organic carbon (DOC), dissolved inorganic N (DIN), dissolved organic N (DON), and reduced metal species (Du Laing et al 2009;Yabusaki et al 2017). Past work has shown that both trace elements and organo-metal complexes, like methylmercury, can be mobilized in Delta soils (Alpers et al 2014;Bachand et al 2019;Stumpner et al 2015). As such, island drainage in the Delta may contribute seasonally important fluxes of both oxidized and reduced N species as well as other macronutrients and trace elements mobilized in wet-dry cycled NRZs.…”
Section: Introductionmentioning
confidence: 99%